Passive control of instability of flexible panels in a mean flow - Tan, Ben Hoea (Curtin University, 2017)
A hybrid of theoretical and computational methods is developed and used to show that localised stiffness added to flexible panels can reduce their susceptibility to flow-induced damage caused by static- and flutter-type instabilities of the panel. Both two- and three-dimensional flow-structure systems are studied with the added stiffness respectively introduced by added springs or a narrow stiffening strip. For two-dimensional systems, a genetic algorithm is developed to optimise the positioning of the added stiffness.